PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR PRISMA DANA MANADO - MAKALUAS, CHRISTIAN G.; Pio, Riane J.; Sumampouw, Harry J. (Sam Ratulangi University, 2017)
Every company should be able to anticipate any changes that arise. Anticipation isintended so that the company can achieve its goals without any disruption and obstacles.Important things to note in the relationship is job satisfaction Because the level ofsatisfaction will be able to improve employee morale, so it can be concluded that therelationship between employees with the company into a reciprocal relationship. At PTBPR Prisma Dana Manado. Robbins (2001).